The Broken Generational Contract in Europe: Generous transfers to the elderly population, low investments in children - Bernhard Hammer; Tanja Istenič; Lili Vargha (Intergenerational Justice Review)
Based on European National Transfer Accounts data from 2010, this paper quantifies and evaluates the balance of intergenerational transfer flows in 16 EU countries, including transfers in the form of unpaid household work. On average, the value of net transfers received by a child amounts to sixteen times the labour income of a full-time worker, and the net transfers received by an elderly person to six times the labour income of a full-time worker. Intergenerational transfers can be regarded as the reciprocal exchange between two generations: the size of the transfers to the child generation determines their potential to generate income and finance public transfers to the elderly population once they enter employment. We develop and calculate an indicator to analyse if there is a balance between transfers to children and transfers expected by the elderly population. The results indicate that in most of the analysed countries the human capital investments in children are far too low to finance the generous transfers to the elderly population in the future.